Contribution of different food groups to the energy intake and weight status of adults: a cross-sectional study in a Malaysian public university - Fokeena, W. B.; Jamaluddin, R.; Khaza'ai, H. (Asian Network for Scientific Information, 2015)
Similar to other countries, Malaysia is not spared from the epidemic of obesity. The fundamental cause of obesity is an imbalance between energy intake and expenditure in which diet is a key, modifiable risk factor. While the food and nutrient intake of Malaysian adults is documented, data on the extent to which each food group contributes to total calorie ingested has not been reported to date. A cross-sectional study was conducted among Malaysian adults (n = 360) aged 18-58 years in a public university. Through face-to-face interview, nutrient intake data was collected using a previously validated food frequency questionnaire. The calorie acquired from different food groups was calculated as a percentage of total calorie intake. Body weight, height and waist circumference were also measured. Food group-wise, the highest calorie derived from vegetables, drinks and confectioneries were by normal weight, obese and overweight participants, respectively. Positive correlations were established between percentage of calorie from eggs and waist circumference (p = 0.035) and percentage of calories from sauces and body mass index (p = 0.013). Percentage of calorie from drinks was positively correlated with all three measures of adiposity, namely; body weight (p = 0.010), body mass index (p = 0.044) and waist circumference (p = 0.020). Adiposity was associated with intake of a larger amount of calories from drinks, confectioneries as well as from eggs and sauces and consumption of lesser calories from vegetables. Such a dietary pattern of overweight and obese individuals can predispose them to health complications such as type 2 diabetes, hypertension and cardiovascular diseases.